2010
DOI: 10.1097/mpg.0b013e3181ea0092
|View full text |Cite
|
Sign up to set email alerts
|

Increased Heat Shock Protein 72 Expression in Celiac Disease

Abstract: The increased expression and altered localization of HSP72 in CD indicate that HSP72 should have a role in protection against gliadin-induced cytotoxicity. HSP72 may exert antiapoptotic effect and contribute to preservation of intestinal epithelial barrier integrity. Moreover, HSP72 as a ligand of TLR2 and TLR4 may promote innate immune responses and warn the cells of the potential injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Elevated HSP70 mRNA and iHSP70 levels were observed in the duodenal mucosa of both untreated and treated children with celiac disease. 106 Importantly, evidence of iHSP70 involvement and junctional redistribution in alterations induced by wheat gliadin in a Caco2 model for celiac disease has been reported recently. 53 However, a 3-day challenge with wheat gluten in celiac and nonceliac patients was insufficient to demonstrate causal modulation of HSP70 gene expression or protein concentrations in duodenal biopsies.…”
Section: Inflammatory Bowel Disease and Celiac Diseasementioning
confidence: 99%
“…Elevated HSP70 mRNA and iHSP70 levels were observed in the duodenal mucosa of both untreated and treated children with celiac disease. 106 Importantly, evidence of iHSP70 involvement and junctional redistribution in alterations induced by wheat gliadin in a Caco2 model for celiac disease has been reported recently. 53 However, a 3-day challenge with wheat gluten in celiac and nonceliac patients was insufficient to demonstrate causal modulation of HSP70 gene expression or protein concentrations in duodenal biopsies.…”
Section: Inflammatory Bowel Disease and Celiac Diseasementioning
confidence: 99%
“…The authors concluded that HSP70-1 gene might be a component of the high risk haplotype, playing a role as an additional predisposing gene for coeliac disease (Ramos-Arroyo et al, 2001). Our research group first examined the expression of HSP72, a member of HSP70 family in the duodenal mucosa of children with coeliac disease (Sziksz et al, 2010). We demonstrated increased mRNA expression and protein levels of HSP72 in their duodenal mucosa localized mainly in the villous enterocytes and in the immune cells of the lamina propria.…”
Section: Hsps In Coeliac Disease: Recent Research Resultsmentioning
confidence: 99%
“…The presence of epithelial stress in CD is indicated by the expression of heat shock proteins (Sziksz et al, 2010), the up-regulation of stress-inducible nonclassical MHC class I molecules, which are the main ligands for NKG2D and CD94/NKG2C (Meresse et al, 2004;Meresse et al, 2006;Hue et al, 2004) and HLA-E on IECs, and the up-regulation of IL-15 (Mention et al, 2003;Jabri et al, 2002), which acts as a major co-stimulatory molecule for the NKG2D-mediated cytolytic pathway (Meresse et al, 2004;Tang et al, 2009). One major inducer of HLA-E is IFNgamma (Rinke de Wit et al, 1990), which is highly secreted by CD IE-CTLs (Forsberg et al, 2007) and inflammatory Lp CD4 + T cells in the presence of IL-15 (DePaolo et al, 2011).…”
Section: Nk Cell Reprogramming Of Tcrαβ Intraepithelial Cytotoxic T Lmentioning
confidence: 99%